# Solving Systems of Equations by Elimination

## Solving Systems of Equations by Elimination

3) x − y = 11
2x + y = 19

6) 8x + y = −16
−3x + y = −5

10) −4x + 9y = 9
x − 3y = −6

12) −7x + y = −19
−2x + 3y = −19

Guest
Guest

## Re: Solving Systems of Equations by Elimination

Using elimination you simply subtract the bottom equation from the top.

3) x-y=11
2x+y=19

For that problem you would do

x-y=11
-(2x+y=19)
-x-2y=-8

I put the original part in parenthesis to show that it's not -2x, but everything is subtracted from the x-y=11.

x-2x=-x, -y-y=-2y, 11-19=-8.

6) 8x+y=-16
-3x+y=-5

8x+y=-16
-(-3x+y=-5)
11x=-11
x=-1

8x-(-3x)=11x. y-y=0, so y is cancelled out of the equation. -16-(-5)=-11. 11x=-11. Divide both sides of the equation by 11 and you get x=-1.

Try the last two on your own.

10) -4x+9y=9
x-3y=-6

-4x+9y=9
-(x-3y=-6)
Spoiler:
-5x+12y=15

12) -7x+y=-19
-2x+3y=-19

-7x+y=-19
-(-2x+3y=-19)
Spoiler:
-5x-2y=0

_________________
I love Bailey, Rise, Rawr (and her twin whose hair flips the wrong way), and Starr. They are my best friends ever. But I love Bailey the most because nobody can compare to her.

That-Awkward-Kid

Posts : 649
Join date : 2011-03-10
Age : 21
Location : Insideout

uhh im confuse

Guest
Guest

## Re: Solving Systems of Equations by Elimination

What are you confused about? Sorry, I was trying to make it less complicated :P

_________________
I love Bailey, Rise, Rawr (and her twin whose hair flips the wrong way), and Starr. They are my best friends ever. But I love Bailey the most because nobody can compare to her.

That-Awkward-Kid

Posts : 649
Join date : 2011-03-10
Age : 21
Location : Insideout

getting y and x

Guest
Guest

## Re: Solving Systems of Equations by Elimination

If you don't mind my helping. I see the problem... This is rather easy math here... I'll take 6 there as an example.

6) 8x + y = −16
−3x + y = −5

So you want to arrange it as a subtraction equation as Guard did right? So it would be:

-3x+y=-5
-(8x+y=-16)
________

You'll notice that subtracting the bottom y with the top y gets rid of them. The leaves you with:

-11x=11 which means
x=-1

Then you take what you get for x and put it into the original equations, for example, putting it back into the first equation would look like:

8x + y = −16
8(-1)+y=-16
-8+y=-16
y=-16+8
y=-8

Though to be honest... it has been some... 4 or 5 years since I've had to do this math... So I'm not sure... But you should try subbing the x value that I found into the other equation... You should get the same thing I got for the one that I just tried above. You should get y=-8, I checked it, but you try it.

Last edited by JENOVA's SOLDIER on Sat Feb 04, 2012 10:32 pm; edited 1 time in total

JENOVA's SOLDIER
Beginner

Posts : 96
Join date : 2012-01-26
Age : 24

## Re: Solving Systems of Equations by Elimination

I'm not even this far into math yet. So I have no clue. Lol

Wolves-Rule1

Posts : 4289
Join date : 2011-07-26
Age : 20
Location : Small town USA. Population 477

## Re: Solving Systems of Equations by Elimination

I was right except for my last bit of math. Sorry, I'll go fix it.

Edit: There all better. I messed up the signs and screwed myself up lol. It happens to everyone

JENOVA's SOLDIER
Beginner

Posts : 96
Join date : 2012-01-26
Age : 24

lol nova

Guest
Guest

## Re: Solving Systems of Equations by Elimination

what do with fraction like if x or y your fraction

Guest
Guest